The effectiveness of spiritual education on the uncertainty of illness in hemodialysis patients - Rauzah, Miftahul; Husna, Cut; Syarif, Hilman (KHD-Production, 2025)
Chronic kidney disease is a progressive condition that requires long-term treatment with hemodialysis. Routine and invasive hemodialysis not only has an impact on the physical aspects of the patient, but also causes psychological, social, and spiritual uncertainty of illness. Uncertainty of illness related to health conditions requires adaptation to changes during the hemodialysis process, including negative psychosocial impacts. Spiritual education consisted of belief and the power of prayer, dzikir (remembrance of Allah) therapy, and enhancing healing motivation. This study aimed to examine the effectiveness of spiritual education in reducing the uncertainty of illness among hemodialysis patients. A quasi-experimental design with a pretest-posttest control group design was employed. The sample comprised 68 respondents divided equally into an intervention and a control group, with 34 respondents/group. The instrument used to measure uncertainty of illness was the Mishel Uncertainty of Illness Scale (MUIS-C, comprising 22 items in a five-point Likert scale. Data analyzed using an independent t-test and a Mann-Whitney U-test. The study results showed a significant difference in the score uncertainty of illness by using spiritual education in hemodialysis patients between the intervention and control groups, with mean ranks of 45.76 and 23.24 (p<0.001), respectively. Interventional spiritual education through an Islamic-based approach showed a significant effect in reducing the uncertainty of illness in hemodialysis patients. These findings suggest that spiritual education may be implemented in nursing interventions to reduce the uncertainty of illness among patients undergoing hemodialysis and may serve as a valuable component in the holistic care of chronic illness.